If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + -32 = 16 + -12x Reorder the terms: -32 + -9x = 16 + -12x Solving -32 + -9x = 16 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -32 + -9x + 12x = 16 + -12x + 12x Combine like terms: -9x + 12x = 3x -32 + 3x = 16 + -12x + 12x Combine like terms: -12x + 12x = 0 -32 + 3x = 16 + 0 -32 + 3x = 16 Add '32' to each side of the equation. -32 + 32 + 3x = 16 + 32 Combine like terms: -32 + 32 = 0 0 + 3x = 16 + 32 3x = 16 + 32 Combine like terms: 16 + 32 = 48 3x = 48 Divide each side by '3'. x = 16 Simplifying x = 16
| 12p-4=56p | | 17*(-6)= | | 20b=300 | | 5k(6k+7)=0 | | -6*(-8)= | | -203+10x=61-2x | | 12x+5=-45 | | 12-8x(-6)= | | 12e=216 | | 3/4=12/ | | 8a+6a-2=5 | | (7)(-2)= | | 6x-1+9x+8= | | (3x)(49)=(14x) | | -3(2t+3)=-33 | | 85f=685 | | 5v+x=w^2 | | 15p-5p+4=9 | | -10(s+1)=51 | | 0.72*c=7.5 | | 5x-3+2x=7x+7 | | 48/-16= | | 5x-1=231 | | 3+2(5x+6)=5 | | 5(4s+6)=130 | | h-10=27 | | 8x-19=4-7x | | -1470=-5x-210 | | 8(2l+7)=72 | | -(3+6)+2x=-(6+2)-3.3 | | 14z=18+12z | | -30-29= |